Compressive strength-color change relation in mortars at high temperature - Yüzer, N; Aköz, F; Öztürk, LD (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
Changes in materials' physical, chemical and mechanical properties have to be known to decide whether the buildings exposed to high-temperature effect will be repaired or demolished. In order to carry out the effects of fire and extinguishing on the properties of concrete, mortars with and without silica fume were exposed to different temperatures, such as 100, 200, 300, 600, 900 and 1200 degreesC, and cooled slowly in the air and fast in water in two groups. Flexural and compressive-strength tests were performed on the samples which were cooled up to room temperature and changes in color were determined by using the Munsell Color System. High temperature has caused damages in mechanical properties of mortars with or without silica fume, especially samples which were cooled in water, which showed significant decrease in mechanical strengths at 600 degreesC. In this study, it was observed that the changes in color's hue component and the compressive strength have similarities. Test results show that residual color changes in mortar can give an idea about the effect of high temperatures on the mechanical properties of mortar during a fire. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: color change; compressive strength; high temperature; silica fume; HIGH-PERFORMANCE CONCRETE; Construction & Building Technology; Materials Science